Information and decision-making in system - Bonacin, D.; Bonacin, D. (Acta Kinesiologica, 2008)
The aim of this article was to determine global rules referring to the reaction of objects / system in the conditions of environment with variables. A special methodology was applied and it included the mathematical model of combining three input parameters with six intensities of influence per one on the object and their simultaneous monitoring. The results showed that the object can act in congruence with three vital reactions and their combinatios: 1) On-line: acutely solving the problem (proportional regulation), 2) Common: including relations with other objects (derivation regulation). 3) Batch: long-time accumulating ideas and resources (integration regulation). There are no limits in this model and it is applicable in any kind of possible situations which can be applied in different disciplines. The practical value of this study is the possible application in the wide range of assignements (informatics, kinesiology, medicine, management,…). The results from this study are in a way peculiar and they require a kind of familiarity with global forms of reactions of any object of our interest in some field.